2019
DOI: 10.1093/ofid/ofz159
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Influenza Vaccination on Mortality and Risk of Hospitalization in Patients With Heart Failure: A Systematic Review and Meta-analysis

Abstract: Background Influenza is a major cause of morbidity and mortality in patients diagnosed with heart failure. The aim of this study was to evaluate the effectiveness of influenza vaccination in this population in terms of reduction in all-cause mortality and rate of hospitalization. Methods We conducted a systematic review and meta-analysis using PubMed and EMBASE entries from January of 2000 through April 2018. Publication bias was examined using the Egger’s regression te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 41 publications
3
4
0
2
Order By: Relevance
“…25 Recently, an analysis of high-risk individuals with chronic obstructive pulmonary disease or heart failure showed a benefit of all-cause mortality in the influenza vaccinated group. 26,27 This finding is comparable to our result because all hospitalized participants in our analysis had more than one underlying illness. Moreover, South Korea has a relatively well-organized immunization program with a high vaccination rate;…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…25 Recently, an analysis of high-risk individuals with chronic obstructive pulmonary disease or heart failure showed a benefit of all-cause mortality in the influenza vaccinated group. 26,27 This finding is comparable to our result because all hospitalized participants in our analysis had more than one underlying illness. Moreover, South Korea has a relatively well-organized immunization program with a high vaccination rate;…”
Section: Discussionsupporting
confidence: 90%
“…However, there is a controversy regarding whether the vaccine can certainly reduce mortality 25 . Recently, an analysis of high‐risk individuals with chronic obstructive pulmonary disease or heart failure showed a benefit of all‐cause mortality in the influenza vaccinated group 26,27 . This finding is comparable to our result because all hospitalized participants in our analysis had more than one underlying illness.…”
Section: Discussionsupporting
confidence: 86%
“…Influenza A and B fluctuated simultaneously or alternately. This was consistent with the global influenza trend in recent years and the local influenza situation [15][16][17]. Influenza A and B viruses can infect people of different ages, and children and adolescents were high-risk people with influenza A or B virus infection [18].…”
Section: Discussionsupporting
confidence: 86%
“…11 A systematic review and meta-analysis of 82,354 patients with HF across 8 studies, influenza vaccination was associated with a 31% lower risk of 1-year all-cause mortality. 26 In a Danish nationwide cohort study with 99.8% follow-up, Modin and colleagues reported a 19% lower risk of mortality for vaccinated vs unvaccinated adults with HF. 12 In the current study, we observed a 34% lower risk of all-cause mortality in multivariable-adjusted analyses; a similar risk reduction was observed for cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%